Dynamic metabolic reprogramming of steroidal glycol-alkaloid and phenylpropanoid biosynthesis may impart early blight resistance in wild tomato (Solanum arcanum Peralta) - Shinde, Balkrishna A.; Dholakia, Bhushan B.; Hussain, Khalid; Panda, Sayantan; Meir, Sagit; Rogachev, Ilana; Aharoni, Asaph; Giri, Ashok P.; Kamble, Avinash C. (Plant Molecular Biology, 2017)
Alternaria solani severely affects tomato (Solanum lycopersicum L.) yield causing early blight (EB) disease in tropical environment. Wild relative, Solanum arcanum Peralta could be a potential source of EB resistance; however, its underlying molecular mechanism largely remains unexplored. Hence, non-targeted metabolomics was applied on resistant and susceptible S. arcanum accessions upon A. solani inoculation to unravel metabolic dynamics during different stages of disease progression. Total 2047 potential metabolite peaks (mass signals) were detected of which 681 and 684 metabolites revealed significant modulation and clear differentiation in resistant and susceptible accessions, respectively. Majority of the EB-triggered metabolic changes were active from steroidal glycol-alkaloid (SGA), lignin and flavonoid biosynthetic pathways. Further, biochemical and gene expression analyses of key enzymes from these pathways positively correlated with phenotypic variation in the S. arcanum accessions indicating their potential role in EB. Additionally, transcription factors regulating lignin biosynthesis were also up-regulated in resistant plants and electrophoretic mobility shift assay revealed sequence-specific binding of rSaWRKY1 with MYB20 promoter. Moreover, transcript accumulation of key genes from phenylpropanoid and SGA pathways along with WRKY and MYB in WRKY1 transgenic tomato lines supported above findings. Overall, this study highlights vital roles of SGAs as phytoalexins and phenylpropanoids along with lignin accumulation unrevealing possible mechanistic basis of EB resistance in wild tomato.